EDUKASI PROTOKOL KESEHATAN PENCEGAHAN COVID-19 DI ERA NEW NORMAL PADA KARANGTARUNA PEMUDA PAHLAWAN DI KABUPATEN BATANG - Dani Prastiwi; Metha Anung Anindhita (PENA ABDIMAS : Jurnal Pengabdian Masyarakat, 2021)
Corona Virus Disease - 2019, known as Covid-19, is a growing problem in the world and its impact is felt by more than 200 countries including Indonesia. The best way to prevent and slow down transmission is with good information about Covid-19. Socialization and education about Covid-19 is often provided by the government, but it is still not running optimally, people still ignore the health protocol for preventing Covid-19. Based on these problems, it is necessary to do socialization, provide correct information about Covid-19. Seeing the current situation and conditions, socialization was carried out through online media. The selected media is WhatsApp Group. The education given in this activity is how to correct health protocols in the New Normal Era and making natural hand sanitizers. Keyword : Education, Preventing Covid-19, Hand Sanitizer.